2020
DOI: 10.24843/jei.2020.v06.i02.p02
|View full text |Cite
|
Sign up to set email alerts
|

Improvement Mechanism of Work Oriented by Ergonomic Increase Health Quality and Productivity

Abstract: The aim of this research is to reduce musculoskeletal disorders, work stress, and increase productivity of workers piranti upakara makers by work mechanism improvement using ergonomic work oriented. Through a quasi-experimental using treatment by subject design and randomized pre and post-test group design assessed: (a) improvement mechanism of work oriented by ergonomic reducing musculoskeletal disorders, was recorded by Nordic Body Map Questionnaire; (b) improvement mechanism of work oriented by ergonomic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Arnita et al (2020) point out that ergonomics influences businesses in terms of disturbance, quality, and productivity. Nevertheless, various authors have suggested that there exists an intersection between productivity, quality and ergonomics(Olabode & Adesanya, 2017; Alveset al, 2019; Rizki, Ushada & Pamungkas, 2019).…”
mentioning
confidence: 99%
“…Arnita et al (2020) point out that ergonomics influences businesses in terms of disturbance, quality, and productivity. Nevertheless, various authors have suggested that there exists an intersection between productivity, quality and ergonomics(Olabode & Adesanya, 2017; Alveset al, 2019; Rizki, Ushada & Pamungkas, 2019).…”
mentioning
confidence: 99%